Understanding Key Influences on Consumer Repurchase Decisions in Fashion Retail SME Stores - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Pratiwi, I Gusti Ayu Made Dian; Meryawan, I Wayan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study examines the effects of product quality, word of mouth (WOM), and store image on consumer repurchase decisions at Dewa Ayu Shop in Klungkung, Bali. Recognizing the essential role of repurchase decisions for business sustainability, this research investigates both individual and combined impacts of these factors on consumer loyalty. Data were collected from 96 respondents through purposive sampling, analyzed using reliability and validity assessments, classical assumption testing, multiple linear regression, determination analysis, t-tests and F-test to evaluate simultaneous and partial influences. Results indicate that product quality, WOM, and store image each positively and significantly impact repurchase decisions, both independently and simultaneously. This study contributes to marketing scholarship by integrating these factors into a cohesive model of consumer repurchase drivers, highlighting the interaction between product quality and brand perception in customer retention. For retail managers, the findings underscore the importance of ensuring high product quality, fostering positive WOM, and enhancing store image, offering actionable insights to build customer loyalty and support competitive advantage in dynamic retail markets.